2014
DOI: 10.1103/physrevb.89.121301
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism and impurity band in a magnetic semiconductor: InMnP

Abstract: We have synthesized ferromagnetic InMnP, a member of III-Mn-V ferromagnetic semiconductor family, by Mn ion implantation and pulsed laser annealing. Clear ferromagnetic hysteresis loops and a perpendicular magnetic anisotropy are observed up to a Curie temperature of 42 K. Large values of negative magnetoresistance and magnetic circular dichroism as well as anomalous Hall effect are further evidences of a ferromagnetic order in InMnP. An effort is made to understand the transport mechanism in InMnP using the t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 36 publications
5
22
0
2
Order By: Relevance
“…• Charge order of high-Tc Superconductors (Blanco-Canosa et al, 2013;Comin et al, 2014;da Silva Neto et al, 2014;Fink et al, 2009;Ghiringhelli et al, 2012) • Coupling of electronic / lattice degrees of freedom in multiferroic materials (Glavic et al, 2013;Partzsch et al, 2011;Schierle et al, 2010;Schmitz-Antoniak et al, 2013;Skaugen et al, 2015) • Microcrystals of novel materials (Leininger et al, 2011;Matsuda et al, 2015) • Interfacial electronic properties in heterostructures (Frano et al, 2013;Wadati et al, 2009) • Element-speci c magnetic hysteresis loops (Radu et al, 2012) • Single molecular magnets (Bernien et al, 2015;Hermanns et al, 2013) • Electronic depth pro les • Electronic ground states and phase transitions in correlated materials (Schmitz et al, 2014;Strigari et al, 2013;Willers et al, 2012Willers et al, , 2011 • Magnetic clusters in carbon nanotubes (Shiozawa et al, 2015) • Nanoparticles for medical applications (Graf et al, 2015) • Magnetic semiconductors (Khalid et al, 2014) …”
Section: Applicationsmentioning
confidence: 99%
“…• Charge order of high-Tc Superconductors (Blanco-Canosa et al, 2013;Comin et al, 2014;da Silva Neto et al, 2014;Fink et al, 2009;Ghiringhelli et al, 2012) • Coupling of electronic / lattice degrees of freedom in multiferroic materials (Glavic et al, 2013;Partzsch et al, 2011;Schierle et al, 2010;Schmitz-Antoniak et al, 2013;Skaugen et al, 2015) • Microcrystals of novel materials (Leininger et al, 2011;Matsuda et al, 2015) • Interfacial electronic properties in heterostructures (Frano et al, 2013;Wadati et al, 2009) • Element-speci c magnetic hysteresis loops (Radu et al, 2012) • Single molecular magnets (Bernien et al, 2015;Hermanns et al, 2013) • Electronic depth pro les • Electronic ground states and phase transitions in correlated materials (Schmitz et al, 2014;Strigari et al, 2013;Willers et al, 2012Willers et al, , 2011 • Magnetic clusters in carbon nanotubes (Shiozawa et al, 2015) • Nanoparticles for medical applications (Graf et al, 2015) • Magnetic semiconductors (Khalid et al, 2014) …”
Section: Applicationsmentioning
confidence: 99%
“…The extreme representatives are (Ga,Mn)P and (In,Mn)P, in which the Mn energy levels are located 400 meV and 220 meV above the valence-band edge, respectively, compared to 110 meV for (Ga,Mn)As. Both materials exhibit hopping conduction [64,65].…”
Section: B Phosphorus Co-alloyingmentioning
confidence: 99%
“…Indeed, the XMCD signal also shows a similar temperature dependent behavior as the magnetization measured by SQUID-VSM. 16 Both methods probe the same ferromagnetic phase. Therefore, we can prove that the ferromagnetism in InMnP is intrinsic and due to substituted Mn ions.…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…4,15 Recently, we have shown that ferromagnetic order can be induced in InMnP with a Mn concentration which is comparable to that of GaMnAs and GaMnP. 16 The aim is to study a system that has the Mn acceptor level in between GaMnAs and GaMnP compounds in order to shed light on the impurity versus valence band debate in III-V semiconductors. InMnP is the most favourable choice to study this effect as it has a bandgap of 1.34 eV and an isolated Mn energy level of 220 meV.…”
Section: Introductionmentioning
confidence: 99%